(3eHGOF Yde GdEMUGA hJWHjbGJg aj GdeLGdjf GdJQHhj hGdELJeGYj (B/s - (3MehOj, SYOj TGcQs ((3YeGf(B: s (3GdOGQ GdYdejI GdOhdjI(B, s, 2000)
(3GdEMUGA hCgejJg aj GdYdhe GdELJeGYjI hGdJQHhjI(B-(3COhGJ GdHMK(B-(3LOhdI GdHjGfGJ GdEMUGFjI(B-(3GdYQV GdHjGfj(B-(3ebGjjS GdfRYI GdeQcRjI(B- (3ebGjjS GdJTJJ(B-(3GdYjfGJ(B-(3GdEQJHGW hGdEfMOGQ(B-(3ENJHGQGJ GdOdGdI GdEMUGFjI(B-(3GdEMUGAGJ GdMjhjI hebGjjSgGs
(3HHdjhZQGajG(B: (3U(B. 258 (3cTGa U(B. 260s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEMUGA GdhUajs; (3GdYdhe GdELJeGYjIs